Removal of heavy metal ions from water using nanocellulose-based membranes derived from macroalgae Chara corallina - Yousif, Yasir; Hassan, Omar; Ibraheem, Ibraheem J. (Brawijaya University, 2024)
Chara corallina is a freshwater macroalgae found in aquatic-terrestrial boundary environments. Their cellulose fibers have a crystallinity and biosynthesis similar to those of terrestrial plants. The algal nanocellulose (NC) was prepared through a series of chemical treatments, including alkaline, bleaching, grinding, and acid hydrolysis. The X-ray diffraction (XRD) crystallinity index of nanocellulose was 85.64%. The cellulose nanocrystals are seen in the form of nanorods, and the specific surface area of the sample of NC found was 5.823 m2g-1. The study aimed to test the effectiveness of a nanocellulose composite membrane in removing heavy metal ions, specifically cadmium (Cd), nickel (Ni), and lead (Pb) ions, from an aqueous solution. A vacuum filtration unit was used for the experiment, where up to five filter layers of composite membranes were examined for their ability to remove heavy metal ions. The results showed that the highest removal rates of Cd2+, Ni2+, and Pb2+ ions were 98.20%, 95.15%, and 93.80%, respectively, when using five layers of membranes of NC with the adsorbent dose set at 20 ppm. Cellulose and its derivatives are essential in sustainable technology for wastewater treatment, as they demonstrate exceptional performance in removing various types of pollutants, including heavy metals, dyes, and other pollutants. Cellulose is preferred due to its low cost, biodegradability, eco-friendliness, and simple surface modification.